Exploring Single-Mother College Students' Perceptions of Their College-Related Experiences and of Campus Services. Issue 3 (2nd September 2018) - Lindsay, Theresa N.; Gillum, Nerissa LeBlanc
Abstract: The purpose of this qualitative study was to explore single-mother college students' perceptions of their college-related experiences and to learn about campus services related to these experiences that could help them during their college journey. Ten single mothers were interviewed using a semi-structured interview guide. Five themes emerged from the data: mothers are motivated by their children, mothers are managers, mothers are time pressured, mothers want the university to consider them as individuals, and mothers want the university to consider their children. Study limitations, future research, and recommendations for policy and practice were presented.